2011
DOI: 10.1111/j.1440-1827.2011.02765.x
|View full text |Cite
|
Sign up to set email alerts
|

RON is associated with tumor progression via the inhibition of apoptosis and cell cycle arrest in human gastric cancer

Abstract: The recepteur d'origine nantais (RON) receptor tyrosine kinase is overexpressed in epithelial cancers, including gastric cancer. The aims of the present study were to evaluate whether RON affects tumor cell behaviors and oncogenic signaling pathways, and to document the relationship of its expression with various clinicopathological parameters in gastric cancer. The biological role of RON in tumor cell behaviors and oncogenic signaling pathways was investigated by using small interfering RNA in gastric cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…Our results suggested that the knockdown of RON inhibited cell proliferation (Figure 3A,C), cell migration (Figure 5A,B), and cell invasion (Figure 6A,B) in AGS and MKN-28 cells. Song et al previously reported that RON is associated with cell cycle arrest in gastric cancer cells [44]. In this study, knockdown of RON also markedly induced G1 arrest in AGS cells (Figure 4B).…”
Section: Resultssupporting
confidence: 73%
“…Our results suggested that the knockdown of RON inhibited cell proliferation (Figure 3A,C), cell migration (Figure 5A,B), and cell invasion (Figure 6A,B) in AGS and MKN-28 cells. Song et al previously reported that RON is associated with cell cycle arrest in gastric cancer cells [44]. In this study, knockdown of RON also markedly induced G1 arrest in AGS cells (Figure 4B).…”
Section: Resultssupporting
confidence: 73%
“…Several studies have suggested that RON is associated with apoptosis in various cancer cells (42,43). However, the impact of RON on apoptosis in human bladder cancer is not reported.…”
Section: Discussionmentioning
confidence: 99%
“…RON signaling has been shown to promote apoptotic resistance in multiple preclinical cancer models, including thyroid, gastric, and colon cancer 18,19,70 . In the context of pancreatic cancer, subcutaneous L3.6pl-induced tumors treated with a RON monoclonal antibody resulted in a 1.3-fold increase in apoptosis compared with the control group, assessed by TUNEL staining (p<0.03) 51 .…”
Section: Apoptotic Resistancementioning
confidence: 99%